Síntese e caracterização de nanocompósitos de poliuretano/ Ni-talco - Prado, Manoela Argenton (2014)
The growth of the polymer market leads to new application niches for these materials with present different properties when compared to the conventional ones, such as composites and nanocomposites, making key the search and the development of these products. Polyurethanes (PUs) are among the most versatile polymers in the world today. To improve the performance of a polyurethane, a common method is to incorporate fillers into the polymer, such as inorganic particles. Thus, this work proposes a study of obtaining and comparing PU nanocomposites by in situ polymerization using natural inorganic filler such as talc and synthetic talc (Ni-talc). The quantities defined Ni-talc were 0.5%, 1%, 2%, 3% and 5% on the mass of polyurethane formed during the polymerization reaction. To follow the results of the technical Infrared Spectroscopy were used Fourier transform (FTIR), differential scanning calorimetry (DSC), Thermogravimetric Analysis (TGA), Gel Permeation Chromatography (GPC), dynamic mechanical analysis (DMTA), Microscopy Scanning Electron (SEM), Analysis of X-Ray Diffraction (XRD) and Analysis of Specific Surface Area (BET). The XRD results showed that intercalation of polymer matrix in the nanocomposites structure. The Ni-talc exhibited better thermal properties when compared to natural talc. The nanocomposites with 0.5, 1 and 2% Ni-talc showed the best strain results in low deformation volues in relation to the pure PU, while the stress-strain results from natural talc nanocomposite shows higher strain values at higher deformation.